Analysis of factors related to stress levels in outpatients with diabetes mellitus and hypertension during the Covid-19 pandemic in Aceh Besar Regency - Yanti, Cut Aini Fauzi; Ichwansyah, Fahmi; Hermansyah, Hermansyah; Marthoenis, Marthoenis; Abdullah, Asnawi (Science Midwifery, 2024)
The prognosis of COVID-19 is influenced by age and comorbidities such as hypertension, diabetes mellitus (DM), pulmonary diseases, and obesity. Observations have found that patients who test positive for the coronavirus often experience anxiety and have high stress levels, particularly among outpatients at health centers. This study aims to analyze the factors related to stress levels in outpatients with DM and hypertension during the COVID-19 pandemic at Krueng Barona Jaya Health Center, Aceh Besar Regency. This quantitative research employs a cross-sectional study approach. The sample consists of 111 individuals out of a total of 154 outpatients with DM and hypertension in the working area of Krueng Barona Jaya Health Center, Aceh Besar Regency, selected through stratified proportional random sampling. Data collection was conducted in the working area of Krueng Barona Jaya Health Center from August 4 to August 10, 2022, using questionnaires distributed to the respondents. The statistical test used was logistic regression with STATA software. The study results showed that 45 individuals (45.04%) experienced moderate stress levels. Bivariate analysis revealed a partial relationship between knowledge, family support, and income with the stress levels of outpatients with DM and hypertension during the COVID-19 pandemic at Krueng Barona Jaya Health Center, Aceh Besar Regency (p<0.05).